Effect of aerobic water exercise during pregnancy on epidural use and pain: A multi-centre, randomised, controlled trial. (December 2021) - Carrascosa, María del Carmen; Navas, Araceli; Artigues, Catalina; Ortas, Silvia; Portells, Elena; Soler, Aina; Bennasar-Veny, Miquel; Leiva, Alfonso; ,
Abstract: Objective: The physical and psychological benefits of exercise during pregnancy are well established. However, the impact of exercise on pain during labour and the use of epidural analgesia has been less explored. The main aim of this study was to analyse the effectiveness and safety of moderate aerobic water exercise by pregnant women on the subsequent use of epidural analgesia during labour, induction of labour, mode of delivery, and pain perception. Design: A multi-centre, parallel, randomised, evaluator blinded, controlled trial in a primary care setting. Setting: Primary care centres in a health district of a tertiary obstetric metropolitan hospital in Mallorca, Spain. Participants: Pregnant women (14 to 20 weeks' gestation) who had low risk of complications. Methods: Three hundred and twenty pregnant women were randomly assigned to two groups: women who practiced moderate aquatic aerobic exercise with usual antenatal care, and those who received usual prenatal care alone. The gynaecologist, anaesthesiologist and midwife who assisted the women during labour were blinded to group allocations. Principal outcome: use of epidural analgesia during labour. Other outcomes: use of epidural analgesia before 6 cm cervical dilation, labour pain, type of delivery, time of active labour, episiotomy or perineal tear, and induction of labour. Results: The exercise program did not affect the use of epidural analgesia (OR = 0.79, 95% CI = 0.44 to 1.40), vaginal delivery (OR = 1.35, 95% CI = 0.73 to 2.41), or caesarean section (OR = 0.94, 95% CI = 0.47 to 1.89). However, women in the exercise group reported less pain during labour (mean difference: –0.6, 95% CI = –1.11 to –0.09). The two groups (moderate aquatic aerobic exercise versus usual antenatal care) showed no significant differences in maternal or newborn adverse events. Conclusion: Aquatic aerobic exercise during pregnancy had no effect on the use of epidural analgesia during labour, whereas pain perception was lower after aquatic exercise compared to usual care in pregnancy. The intervention was safe for pregnant women and their newborns.